2004
DOI: 10.1104/pp.103.038372
|View full text |Cite
|
Sign up to set email alerts
|

Production of Coumaroylserotonin and Feruloylserotonin in Transgenic Rice Expressing Pepper Hydroxycinnamoyl-Coenzyme A:Serotonin N-(Hydroxycinnamoyl)transferase

Abstract: Transgenic rice (Oryza sativa) plants were engineered to express a N-(hydroxycinnamoyl)transferase from pepper (Capsicum annuum), which has been shown to have hydroxycinnamoyl-CoA:tyramine N-(hydroxycinnamoyl)transferase activity, a key enzyme in the synthesis of hydroxycinnamic acid amides, under the control of constitutive maize (Zea mays) ubiquitin promoter. The transgenic rice plants require foliar application of amines to support synthesis of hydroxycinnamic acid amides, suggestive of limiting amine subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 45 publications
3
49
0
Order By: Relevance
“…7C). The K m values in the SHT-Y149F for two acyl donors, p-coumaroyl-CoA and feruloyl-CoA, were 25 and 5 mM, respectively, which are comparable to those measured in wild-type SHT (Jang et al, 2004). This indicates that the mutation in Tyr-149 into Phe-149 does not alter acyl donor substrate binding or catalysis.…”
Section: Catalytic Specificities Of Point-mutated Sht Proteinssupporting
confidence: 62%
See 3 more Smart Citations
“…7C). The K m values in the SHT-Y149F for two acyl donors, p-coumaroyl-CoA and feruloyl-CoA, were 25 and 5 mM, respectively, which are comparable to those measured in wild-type SHT (Jang et al, 2004). This indicates that the mutation in Tyr-149 into Phe-149 does not alter acyl donor substrate binding or catalysis.…”
Section: Catalytic Specificities Of Point-mutated Sht Proteinssupporting
confidence: 62%
“…The two highly similar THT isogenes identified have been demonstrated to encode two different enzymes, THT and SHT. In addition to its presence in the Solanaceae, THT activity has been observed in other plant families, such as the Papaveraceae (Yu and Facchini, 1999) and Gramineae (Ishihara et al, 2000;Jang et al, 2004), but no gene structure data have been reported as yet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While BAHD proteins are responsible for the acylation of aliphatic and arylmonoamine acceptors, GNAT enzymes are active on arylamines (Bassard et al, 2010). Although they are from two distinct protein families that show low sequence identity, the BAHD N-acyltransferases, Os-THTs and Os-TBTs, identified in our study demonstrate that proteins from both families can act on aryldiamines (Tables 2 and 3; Jang et al, 2004;Kang et al, 2006). Comparing the specificity of the enzymes between the two families showed that whereas GNAT members are highly specific for tyramine, the BAHD enzymes may be regarded as bifunctional tryptamine/tyramine N-acyltransferases.…”
Section: Discussionmentioning
confidence: 91%